All Art Now- 1st International Video Art Festival 2009 / (3egQLGf Gdaf GdBf GdOhdj GdChd ddajOjh Gdaf GdBf, OeTb, ShQjGs - Abir Boukhari; Nasrine Boukhari (Damascus; All Art Now, 2009)
Exhibition catalog.
English; Arabic
Keywords: N4390-5098 Exhibitions; Video Art